Dietary NaCl affects bleomycin-induced lung fibrosis in mice. (26th November 2017) - Chen, Wensheng; Pilling, Darrell; Gomer, Richard H.
ABSTRACT: Purpose: High levels of NaCl in the diet are associated with both cardiac and renal fibrosis, but whether salt intake affects pulmonary fibrosis has not been examined. Aim of the Study: To test the hypothesis that salt intake might affect pulmonary fibrosis. Materials and Methods: Mice were fed low, normal, or high salt diets for 2 weeks, and then treated with oropharyngeal bleomycin to induce pulmonary fibrosis, or oropharyngeal saline as a control. Results: As determined by collagen staining of lung sections, and protein levels and cell numbers in the bronchoalveolar lavage (BAL) fluid at 21 days after bleomycin, the high salt diet did not exacerbate bleomycin-induced fibrosis, while the low salt diet attenuated fibrosis. For the bleomycin-treated mice, staining of the post-BAL lung sections indicated that compared to the regular salt diet, high salt increased the number of Ly6c-positive macrophages and decreased the number of CD11c and CD206-positive macrophages and dendritic cells. The low salt diet caused bleomycin-induced leukocyte numbers to be similar to control saline-treated mice, but reduced numbers of CD45/collagen-VI positive fibrocytes. In the saline controls, low dietary salt decreased CD11b and CD11c positive cells in lung sections, and high dietary salt increased fibrocytes. Conclusions: Together, these data suggest the possibility that a low salt diet might attenuate pulmonary fibrosis.